The Threatened Sense of Security in the Work of Paramedics - Bsoul-Kopowska, Magdalena (Roczniki Nauk Społecznych, 2026)
Emergency medical services are a crucial aspect of any healthcare system, and the work of a paramedic inherently involves a great deal of responsibility and constant risk. This article presents psychosocial safety hazards related to the work of paramedics, focusing in particular on acts of aggression towards paramedics who perform their duties. According to the WHO, up to 38% of healthcare workers experience physical violence. The aim of this study is to estimate the incidence of aggression/violence towards Polish paramedics, examine paramedics’ perceived occupational safety, and determine the impact of the aggressive behavior of patients and their companions on the quality of emergency medical services.